PROGRAM GOVERNMENT PUBLIC RELATIONS UNTUK MENINGKATKAN PARTISIPASI MASYARAKAT KOTA SEMARANG DALAM MENGGUNAKAN LAPOR SEMAR SOLUSI AWP SEBAGAI KANAL PENGADUAN RESMI KOTA SEMARANG SEBAGAI PUBLIC RELATIONS DAN EVENT MANAGER - Nisrina Indriani; Djoko Setudiyab (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
This fieldwork report discusses the use of Government Public Relations strategies, eventactivation, and media publication to increase public awareness and participation toward theLapor Semar Solusi AWP public complaint service in Semarang City. The campaign wascarried out through the Main Event “Cipta Seni Bahana Aspirasi” at CFD Simpang Lima asthe opening activation, followed by a series of outreach activities: Goes to Campus, Goes toSchool, and Goes to RW. The results show significant achievements. The Main Event attracted100 audiences, while the outreach series generated 464 new users. Media publication was alsoeffective through collaboration with 13 Forwakot media outlets, two radio stations, as well aspress releases published on the Lapor Semar and Semarang City Government websites.As the Public Relations and Event Planner, the author managed external communication, mediapublication, and collaboration with schools, faculties, RW communities, and media partners.The author also prepared the rundown, conducted venue surveys, coordinated with Diskominfo,arranged talents, and ensured that the Main Event ran safely, orderly, and in line with campaignobjectives. This report demonstrates that the combination of targeted PR strategies andinteractive event activation effectively strengthens public awareness, trust, and participationtoward the Lapor Semar Solusi AWP service.